Hubungan antara Efikasi Diri dengan Mobilisasi Dini pada Pasien Paska Bedah Mayor - Aisah, Nur Aas; Ropyanto, Chandra Bagus (Holistic Nursing and Health Science, 2022)
Introduction: Self-efficacy affects the ability to perform early mobilization in patients after digestive surgery. The characteristics of pain are different in digestive and major surgical pain. Pain can effect self-efficacy and early mobilization.  The purpose of this study is to analyze the relationship between self-efficacy and early mobilization of major post-surgical patients.Methods: The study used a correlation descriptive design with a cross sectional approach with a total sample of 62 post operation patients aged 21-65 years who were compos mentis. The research instrument for self-efficacy used The General Self-Efficacy Scale (GSE), while early mobilization used Cumulated Ambulation Afternoon (CAS). Data were analyzed used Spearman rho.Results: The results showed that the mean self-efficacy score was 36,56 and the average value of early mobilization was 2.02. The results of correlation test obtained p value=0.172 with r=0.181.Conclusion: The conclusion of this study is that there was no significant relationship between self-efficacy with early mobilization. The suggestion in the study is to examine other factors that can affect early postoperative mosbilization. Keywords: Early Mobilization, Major Post-Surgical, Self-Efficacy.